2021
DOI: 10.3389/fpubh.2021.741030
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Matrix Profile-Guided Attention LSTM Model for Forecasting COVID-19 Cases in USA

Abstract: Background: The outbreak of the novel coronavirus disease 2019 (COVID-19) has been raging around the world for more than 1 year. Analysis of previous COVID-19 data is useful to explore its epidemic patterns. Utilizing data mining and machine learning methods for COVID-19 forecasting might provide a better insight into the trends of COVID-19 cases. This study aims to model the COVID-19 cases and perform forecasting of three important indicators of COVID-19 in the United States of America (USA), which are the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Support vector machine (SVM) is a machine-learning language for classification developed by Vapnik [ 29 ]. Suppose there are two categories of samples: H1 and H2.…”
Section: Methodsmentioning
confidence: 99%
“…Support vector machine (SVM) is a machine-learning language for classification developed by Vapnik [ 29 ]. Suppose there are two categories of samples: H1 and H2.…”
Section: Methodsmentioning
confidence: 99%
“…Liu et al. 18 proposed a novel forecasting algorithm to model and predict the three indicators (hospital admission, confirmed cases and death cases). Vijander et al.…”
Section: Introductionmentioning
confidence: 99%
“…The MP has also been used in anomaly detection on IT operations time series data to address the issue of monitoring IT systems’ Key Performance Indicators [ 13 ]. The MP has offered market analysis based techniques in terms of stock-market financial time series data [ 14 ], while recent research has shown that in predicting COVID-19 cases, a hybrid of the MP and an attention-based long short-term memory (LSTM) model performed best when compared to other models [ 15 ].…”
Section: Introductionmentioning
confidence: 99%